Implementation of Prophetic Leadership in Forming a Differential Learning Culture - Muhammad Shulthon Rachmandhani (Universitas Muhammadiyah Ponorogo, 2023)
This article aims to find the model of prophetic leadership applied by school principals in forming a differentiated learning culture at SDN 01 Taman Madiun, MI Badi'usy Syamsi Dolopo Madiun, and SD Muhammadiyah 1 Ponorogo. The research method used to write this article is multi-site qualitative using the Spreadley model data analysis technique. The results of the study show that: 1) The prophetic leadership model applied at SDN 01 Taman Madiun in building a differentiated learning culture of participatory managerial type based on diagnostic assessment. 2) The prophetic leadership model applied at MI Badi'usy Syamsi Dolopo Madiun in building a differentiated learning culture of the autocratic visionary type based on Qur'anic culture. 3). The prophetic leadership model applied at MI Badi'usy Syamsi Dolopo Madiun in building a team-based, participatory, differentiated learning culture. The results of this study can serve as an example for school principals in forming a differentiated learning culture, because differentiated learning focuses on meeting students' learning needs according to the characteristics and competencies of each student.